AGA682: Turf Management / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (Universiti Teknologi MARA (UiTM), 2020)
This course will provide students with an appropriate technology in identification, cultivation and maintenance of turf grasses. The student will also be exposed to the wide varieties of turf-grass, major insect and disease management.